Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 8 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics - Baldi, Antonio; Considine, John M.; Quinn, Simon; Balandraud, Xavier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems, Volume 8 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the eighth volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Residual Stress Measurements Stress Analysis from Thermal Measurements Damage & Defect Analysis Using Infrared Techniques Inverse Methods in Plasticity Inverse Problem Methodologies in Experimental Mechanics.
Chapter 1.Residual Stresses in Bovine Femurs -- Chapter 2.Experimental Stress Analysis of Unsymmetrical, Irregularly-Shaped Structure Containing an Arbitrarily-Shaped Hole -- Chapter 3.Experimental Stress Analysis of Unsymmetrical, Irregularly-Shaped Structure Containing an Arbitrarily-Shaped Hole -- Chapter 4. A new Denoising Methodology to Keep the Spatial Resolution of IR Images Equal to 1 Pixel -- Chapter 5.Calorific Signature of PLC Bands Under Biaxial Loading Conditions in Al-Mg Alloys -- Chapter 6.How Does Cristallizable Rubber use Mechanical Energy to Deform? -- Chapter 7.Use of Bulge Test Geometry for Material Property Identification -- Chapter 8.Crystal Plasticity Parameter Identification by Integrated DIC on Microscopic Topographies -- Chapter 9.Comparison of Residual Stress Characterization Techniques Using an Interference Fit Sample -- Chapter 10. Influence of Thermographic Image Filtering on Hybrid TSA -- Chapter 11. Optical Analysis of Residual Stress with Minimum Invasion -- Chapter 12.Determination of Constitutive Properties in Inverse Problem by using Airy Stress Function -- Chapter 13.High-speed Infrared Imaging for Material Characterization in Experimental Mechanic Experiments -- Chapter 14.A Spatio-temporal Approach for iDIC-Residual Stress Measurement -- Chapter 15.Detection of Early Stage Material Damage using Thermophysical Properties -- Chapter 16.Repeatability of Contour Method Residual Stress Measurements for a Range of Material, Process, and Geometry -- Chapter 17.System Identification of Structures with Modal Interference -- Chapter 18.Influence of Printing Constraints on Residual Stresses of FDM Parts.
Keywords: Mechanics, Applied; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Computer vision; Materials -- Analysis; Engineering Mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Computer Vision; Characterization and Analytical Technique